First-in-human study of PSMA-targeting agent, [18F]AlF-P16-093: dosimetry and initial evaluation in prostate cancer patients - Zhao, Ruiyue; Ke, Miao; Lv, Jie; Liu, Shaoyu; Liu, Yuheng; Zhang, Jing; Xu, Lifu; Gu, Di; Li, Mingzhao; Cai, Chao; Liu, Yongda; Zeng, Guohua; et al. (European journal of nuclear medicine and molecular imaging, 2024)
Purpose This is a first-in-human study to evaluate the radiation dosimetry of a new prostate-specific membrane antigen (PSMA)-targeted radiopharmaceutical, [ 18 F]AlF-P16-093, and also initial investigation of its ability to detect PSMA-positive tumors using PET scans in a cohort of prostate cancer (PCa) patients. Methods The [ 18 F]AlF-P16-093 was automatically synthesized with a GE TRACERlab. A total of 23 patients with histopathologically proven PCa were prospectively enrolled. Dosimetry and biodistribution study investigations were carried out on a subset of six (6) PCa patients, involving multiple time-point scanning. The mean absorbed doses were estimated with PMOD and OLINDA software. Results [ 18 F]AlF-P16-093 was successfully synthesized, and radiochemical purity was > 95%, and average labeling yield was 36.5 ± 8.3% (decay correction, n = 12). The highest tracer uptake was observed in the kidneys, spleen, and liver, contributing to an effective dose of 16.8 ± 1.3 μSv/MBq, which was ~ 30% lower than that of [ 68 Ga]Ga-P16-093. All subjects tolerated the PET examination well, and no reportable side-effects were observed. The PSMA-positive tumors displayed rapid uptake, and they were all detectable within 10 min, and no additional lesions were observed in the following multi-time points scanning. Each patient had at least one detectable tumor lesion, and a total of 356 tumor lesions were observed, including intraprostatic, lymph node metastases, bone metastases, and other soft tissue metastases. Conclusions We report herein a streamlined method for high yield synthesis of [ 18 F]AlF-P16-093. Preliminary study in PCa patients has demonstrated its safety and acceptable radiation dosimetry. The initial diagnostic study indicated that [ 18 F]AlF-P16-093 PET/CT is efficacious and potentially useful for a widespread application in the diagnosis of PCa patients.